2001
DOI: 10.1046/j.1365-2672.2001.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular genotyping of Cryptosporidium spp. in surface waters in Northern Ireland

Abstract: Aims: To investigate the incidence and genotype of Cryptosporidium parvum oocysts in drinking water sources in Northern Ireland for the period 1996±1999, and to compare conventional and molecular methods of detection. Methods and Results: Four hundred and seventy-four waters were investigated by conventional methods, namely immuno-¯uorescent antibody detection (IFA; 380) and immuno-magnetic separation-IFA (IMS-IFA; 94), of which 14/474 (3%) were positive. Two hundred and fourteen samples (214/474) were also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The SSU rRNA PCR-based method detected Cryptosporidium oocysts in 86% of samples or 82% of all samples and subsamples analyzed, whereas the latter detected oocysts in only 62% of the samples or 70% of all samples and subsamples, despite the fact that many samples and subsamples had more than 0.5 ml of packed pellet volume analyzed by microscopy. Previously, other studies have also shown that PCRbased methods have higher sensitivities than microscopy-based methods such as method 1622/1623 for detecting Cryptosporidium oocysts in water (5,9,10,12,13,24). In the present study, the higher detection rate by PCR occurred largely in samples where microscopy failed to detect any oocysts.…”
Section: Discussionsupporting
confidence: 57%
“…The SSU rRNA PCR-based method detected Cryptosporidium oocysts in 86% of samples or 82% of all samples and subsamples analyzed, whereas the latter detected oocysts in only 62% of the samples or 70% of all samples and subsamples, despite the fact that many samples and subsamples had more than 0.5 ml of packed pellet volume analyzed by microscopy. Previously, other studies have also shown that PCRbased methods have higher sensitivities than microscopy-based methods such as method 1622/1623 for detecting Cryptosporidium oocysts in water (5,9,10,12,13,24). In the present study, the higher detection rate by PCR occurred largely in samples where microscopy failed to detect any oocysts.…”
Section: Discussionsupporting
confidence: 57%
“…However, the data on the annual occurrence of Cryptosporidium sp. in humans in England (8.9 cases per 100,000 persons) (Lowery et al 2001) is higher than in Spain (0.2 cases per 100,000 persons) (Anonymous 2003). This difference may be the result of the prevalence in Spain being underestimated (Montemayor et al 2005).…”
Section: Resultsmentioning
confidence: 94%
“…Recent studies (3,6,8,10,13,14,24) have shown that the use of molecular methods, such as PCR-RFLP, has some advantages over the traditional IFA detection method. This and the previous study (31) clearly indicate that detection of Cryptosporidium in storm water samples by PCR is more sensitive than the IFA method.…”
Section: Discussionmentioning
confidence: 99%
“…This and the previous study (31) clearly indicate that detection of Cryptosporidium in storm water samples by PCR is more sensitive than the IFA method. Other studies have also shown that PCR has higher sensitivities in the analysis of both clinical and environmental samples (3,6,8,10,13,14,24). It is possible that some oocysts present in storm samples were not stained by immunofluorescence due to the loss of surface antigens as a result of long exposure to the adverse environment.…”
Section: Discussionmentioning
confidence: 99%